COPRA experiment and numerical research on the behavior of internally-heated melt pool with eutectic salt. (25th July 2018) - Luo, Simin; Zhang, Yapei; Zhou, Yukun; Tian, Wenxi; Su, GH; Qiu, Suizheng
Highlights: Eutectic salt was used for experimental research on the melt pool behavior. A sudden introduce of cooling and the melt pouring are the most dangerous transient. Power changing exerts obvious impacts on the crust growth below polar angle 30°. Steady-state correlations are qualified to analyze long-term cooling transient. Vortexes could form near the crust region, making an even temperature distribution. Abstract: In-vessel retention (IVR) has been proposed as an effective mitigation strategy during severe accidents in pressurized water reactors (PWRs). To help understand better the application of IVR, the large-scale COPRA facility was used for experimental research and the eutectic salt, i.e. the binary mixture of 50 mol% NaNO3 – 50 mol% KNO3 was selected as the simulant material for corium. Besides, numerical studies were done to capture the detailed flow field information. The experiment studied the effects of a sudden change in boundary condition and the influences of power changes on the transient behaviors and the steady-state characteristics of melt pool. Experimental results show that a sudden introduction of sidewall cooling and the melt pouring are the most threatening factors to the reactor vessel safety, but which can be guaranteed as long as the vessel is kept undamaged during melt pouring phases. Also, power changing won't lead to rapid variation of sideward heat flux, so the correlations for steady state heat transfer calculation are basically qualified to evaluate the reactor safety in analysis of long time cooling. Besides, the power changing only exerts obvious impacts on the crust growth on the curved sidewall inner surface with polar angle below 30°, contrary to which the sideward heat flux is clearly influenced by different power densities only above the angle of 30°. Finally, the numerical simulation results show that vortexes could form near the region where the crust formed, and lead to a more homogeneous temperature distribution; generally, the convection happens between the lower part of melt pool and cooling boundary, with flow velocity at a magnitude of 0.01 m/s.